Penafsiran Ayat-Ayat Al-Qurâan tentang Amanah menurut M. Quraish Shihab - az zainuri, muhammad sahri (Madaniyah, 2018)
Education has an important role in maintaining life on earth, by strengthening and instilling an attitude of trust. Amanah is one of the most basic buildings in interacting with God, human, environment and self. Trust must be formed from the time of childhood because young children are like white paper, so the formation of trustworthy attitude easily is accepted by the child. God gives trust only to man, because only human beings are able to carry it. However, in reality people pay less attention to the mandate.Â  As if the trust is only a responsibility that can be done when it is capable, otherwise if not able not done. In fact, Allah SWT clearly has forbidden humans not to betray and deny a mandate that has been submitted to humans. If a man neglects a mandate, then there will be a destruction in this world. Humans become the benchmark of prosperity on this earth. If the government and leaders are able to carry out the attitude of trust, then the earth will be peaceful and secure.Keyword: interpretation, verses of Quran, Trust